Putting Edmodo Into Classroom: Portraying Learning Management System (LMS) Manifestation - Nasrullah - Nasrullah; Asmi - Rusmanayanti; Elsa - Rosalina; Rahma Pitria Ningsih (Universitas Bengkulu, 2021)
An array of teaching tools have been developed enormously today sparking interest for educators in their instruction. Edmodo, which is also one of the CALL applications that can be accessed online both from computer and mobile telephone is one option for teachers and students and can be operated to post various things related to EFL teaching-learning process. However, many educators are reluctant to embed with them pedagogical function which coming along in the use of Edmodo. This research employed open-ended questionnaire which is spread to English Language Education ULM students who are taking Extensive Reading course. This research contributes to picture out perception in implementing Edmodo as Web-Quest as well Learning Management System (LMS) in online classroom instructional activities. The result of this study shows that the involvement of Edmodo to material delivery still does not encounter the predicted expectation. The limited storing material in the application and lack of feedback of the task through the media are the reasons of the barrier. In conclusion, the use of Edmodo needs to be developed along with the mindset of students centered activities.